A Novel Shell-less Culture System for Chick Embryos Using a Plastic Film as Culture Vessels - Yutaka Tahara; Katsuya Obara (The Journal of Poultry Science, 2014)
The development of shell-less culture methods for bird embryos with high hatchability would be useful for the efficient generation of transgenic chickens, embryo manipulations, tissue engineering, and basic studies in regenerative medicine. To date, studies of culture methods for bird embryos include the whole embryo culture using narrow windowed eggshells, surrogate eggshells, and an artificial vessel using a gas-permeable membrane. However, there are no reports achieving high hatchability of >50% using completely artificial vessels. To establish a simple method for culturing chick embryos with high hatchability, we examined various culture conditions, including methods for calcium supplementation and oxygen aeration. In the embryo cultures where the embryos were transferred to the culture vessel after 55-56 h incubation, more than 90% of embryos survived until day 17 when a polymethylpentene film was used as a culture vessel with calcium lactate and distilled water supplementations. The aeration of pure oxygen to the surviving embryos from day 17 yielded a hatchability of 57.1% (8 out of 14). Thus, we successfully achieved a high hatchability with this method in chicken embryo culture using an artificial vessel.